2012
DOI: 10.1007/s00438-012-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of the efficient industrial fuel-ethanol fermentative Saccharomyces cerevisiae strain CAT-1

Abstract: The Saccharomyces cerevisiae strains widely used for industrial fuel-ethanol production have been developed by selection, but their underlying beneficial genetic polymorphisms remain unknown. Here, we report the draft whole-genome sequence of the S. cerevisiae strain CAT-1, which is a dominant fuel-ethanol fermentative strain from the sugarcane industry in Brazil. Our results indicate that strain CAT-1 is a highly heterozygous diploid yeast strain, and the ~12-Mb genome of CAT-1, when compared with the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 65 publications
5
57
0
1
Order By: Relevance
“…in its lyophilized form. This strain was isolated from industrial processes for ethanol production by Fermentec and Escola Superior de Agricultura Luiz de Queiroz [34]. The lyophilized yeast was stored at a temperature between 1 C and 5 C. For the fermentations, it was weighed and inoculated directly without pre-cultivation.…”
Section: Raw Materials Enzymes and Microorganismmentioning
confidence: 99%
“…in its lyophilized form. This strain was isolated from industrial processes for ethanol production by Fermentec and Escola Superior de Agricultura Luiz de Queiroz [34]. The lyophilized yeast was stored at a temperature between 1 C and 5 C. For the fermentations, it was weighed and inoculated directly without pre-cultivation.…”
Section: Raw Materials Enzymes and Microorganismmentioning
confidence: 99%
“…For example, Magwene et al (2011), based on whole genome sequencing of 11 diploid isolates plus genotyping of nine loci in 18 additional strains, concluded that approximately 60% of strains they examined had modest (> 5,000 sites) to extensive (> 15,000 sites) genomic heterozygosity. Subsequent genome sequencing of additional environmental isolates has led to similar findings (Akao et al, 2011; Babrzadeh et al, 2012; Hyma and Fay, 2013). …”
Section: Evidence For the Genome Renewal Hypothesismentioning
confidence: 67%
“…Bioethanol is an ecological, clean, and renewable biofuel that merge as an option to dismiss the environmental impact of fossil fuels [1]. The predominant microorganisms responsible for the efficient production of ethanol are selected strains of the yeast Saccharomyces cerevisiae [1].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant microorganisms responsible for the efficient production of ethanol are selected strains of the yeast Saccharomyces cerevisiae [1]. In this work we characterize the genome of a natural isolated strain of S. cerevisiae that was selected from a group of yeast because its potential to produce ethanol of first and second generation, comparable with other natural isolated and commercial strains (like Red Fermentis®) [2].…”
Section: Introductionmentioning
confidence: 99%